Caracterização genética e análise da composição química de variedades crioulas de arroz (Oryza sativa L.) - Paz, Dannielle Silva da (2023)
Rice(Oryza sativa L.) is considered one of the most important grains not only for its economic value, but also for its nutritional value. The aim of this research was to carry out molecular characterization, based on microsatellite markers, and to evaluate the chemical composition of creole rice varieties. Forty-three genotypes from the creole rice seed collection of the State University of Maranhão and one improved variety were used. Genomic DNA was extracted and amplified using twenty microsatellite primers. The PCR products were coded for the presence (1) and absence (0) of bands and converted into a binary matrix. Genetic analyses were carried out using specific software. The chemical composition analyzed was dry matter (DM), mineral matter (MM), organic matter (OM), crude protein (CP), total carbohydrates (CP), neutral and acid detergent fiber (NDF and FDA), fat (EE), lignin and starch. Of the twenty primers evaluated, 18 polymorphic markers were detected. The primers RM 270, RM84, RM 87, RM 528, RM 17, RM 231 and RM 434 were considered highly informative, with a PIC between 0.52 and 1.00. The dendrogram showed 11 main clusters, with IX having the largest number of genotypes. The highest average dissimilarity was observed for the Palha Murcha genotype (0.54). The varieties Cutião (2.20) and Palha Murcha (2.30) had the lowest diversity indices. On the other hand, Fininho Branco, Cana Roxa and Codozinho 2 were more genetically diverse (2.83). In terms of chemical composition, the Quilombo Frechal variety had the highest DM content (91.48 %), while the lowest MM content was found in the Asa variety (0.77%). The highest CP content was in the BRS Primavera variety (13.83 %), while the lowest EE content was 0.76 (Ligeiro). The Branco variety had the lowest CHO content. The highest starch content was found in the Cana roxa variety (93.19 %). The Ligeiro Vermelho variety had the highest lignin content (1.53 %). The use of microsatellite molecular markers provided a solid basis for the genetic characterization of the O. sativa genotypes, identifying the genetic similarity between the varieties evaluated, as well as demonstrating genetic variation within clusters, for chemical composition the varieties showed nutritional richness, confirming that the Creole rice present in family farming, even under adverse conditions, showed values similar to improved varieties already described in previous research. The results presented here were considered extremely important in guiding future plant genetic improvement programs.